2007
DOI: 10.1038/sj.ijir.3901627
|View full text |Cite
|
Sign up to set email alerts
|

Role of the soluble guanylyl cyclase α1-subunit in mice corpus cavernosum smooth muscle relaxation

Abstract: Soluble guanylyl cyclase (sGC) is the major effector molecule for nitric oxide (NO) and as such an interesting therapeutic target for the treatment of erectile dysfunction. To assess the functional importance of the sGCa 1 b 1 isoform in corpus cavernosum (CC) relaxation, CC from male sGCa 1 À/À and wild-type mice were mounted in organ baths for isometric tension recording. The relaxation to endogenous NO (from acetylcholine, bradykinin and electrical field stimulation) was nearly abolished in the sGCa 1 À/À C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…However, only the α 1 β 1 and α 2 β 1 heterodimers are catalytically active [31]. Studies suggested that sGCα 1 β 1 is predominantly expressed in CC and is the most important sGC heterodimer responsible for corporal smooth muscle relaxation [32–34]. In aorta from sGCα 1 −/− mice, the resveratrol‐ and quercetin‐induced relaxations were significantly inhibited, confirming the NO/sGC dependency by which polyphenols relax arteries.…”
Section: Discussionmentioning
confidence: 95%
“…However, only the α 1 β 1 and α 2 β 1 heterodimers are catalytically active [31]. Studies suggested that sGCα 1 β 1 is predominantly expressed in CC and is the most important sGC heterodimer responsible for corporal smooth muscle relaxation [32–34]. In aorta from sGCα 1 −/− mice, the resveratrol‐ and quercetin‐induced relaxations were significantly inhibited, confirming the NO/sGC dependency by which polyphenols relax arteries.…”
Section: Discussionmentioning
confidence: 95%
“…The enzyme, which catalyzes the conversion of GTP into cGMP, consists of two different subunits and contains a prosthetic heme group that mediates up to 400-fold activation by NO. Nimmegeers et al (2008) assessed the functional importance of the sGC␣ 1 ␤ 1 isoform in CC from male sGC␣ 1 (Ϫ/Ϫ) and wild-type mice. The relaxation to endogenous NO (from acetylcholine, bradykinin, and electrical field stimulation) was nearly abolished in the sGC␣ 1 (Ϫ/Ϫ) CC.…”
Section: J Nitric Oxide and Cgmp Signalingmentioning
confidence: 99%
“…High concentrations of cGMP produced by activated sGC modulate functions of numerous enzymes, such as cyclic nucleotide phosphodiesterases, cGMP-gated ion channels, and cGMP-dependent protein kinases (PGKs). Recently, the vital importance of sGC for mammalian physiology was directly confirmed by generation of sGC knock-out mice (7)(8)(9). The absence of sGC protein resulted in a significant increase in blood pressure, complete loss of NO-dependent aortic relaxation, and inhibition of platelet aggregation in knock-out animals, which died prematurely at the age of 4 weeks because of severe gastrointestinal disorders (7).…”
mentioning
confidence: 99%
“…Vascular smooth muscle and endothelial cells express predominantly ␣ 1 -and ␤ 1 -subunits (12). The functional importance of ␣ 1 /␤ 1 sGC was demonstrated by the significantly decreased relaxing effects of major vasodilators (acetylcholine, NO, YC-1, and BAY41-2272) in the ␣ 1 sGC knock-out mice of both genders (9). sGC function is affected not only by NO, but also by regulation of the expression of sGC subunits at transcriptional and post-transcriptional levels.…”
mentioning
confidence: 99%